GAMBARAN KEJADIAN BABY BLUES PADA IBU POSTPARTUM DI KOTA MEDAN - Wellina BR Sebayang; Ravika Dewi; Feni Hati Halawa (Jurnal Ilmiah Kebidanan Imelda, 2024)
Postpartum depression in postpartum mothers usually begins with the postpartum blues or baby blues. Baby blues syndrome is often considered not very important and is arely considered, because even if many experience it, it is often only seen as a side effect of fatigue after giving birth. But basically abby blues are very dangerous for the healt of postpartum mothers and also dangerous for their babies. The purpose of this research is to find out how the prevalence of abbay blues in the city of Medan, North Sumatera. The samples taken in this study were 80 postpartum mothers. The method used is descriptive quantitative research with primary data collection through questionnaire interviews according to the Edinburgh Postpartum Depression Scale. The result of study can be stated that many mothers experience baby blues as much as 92,5% of respondents. Mothers who experienced the incidence of baby blues from the age of <20 were 56,25%. As well as the incidence of postpartum blues in primipadra mothers as much as 72,52%. Symptoms of postpartum blues are characterized by the presence of disturbances such as reaction of depression or sadbess, crying,irritability, anxiety, feeling unstable, tending to blame oneself, impaired appetite.